The IPCC and the Politics of Writing Climate Change - Hughes, Hannah (Cambridge University Press, 2025)
Using a new analytical framework, this book examines the history and politics of the Intergovernmental Panel on Climate Change (IPCC), and how this shapes its assessment practice and the climate knowledge it produces. It is indispensable for students and researchers of climate politics, and anyone interested in the IPCC.